Linking habitat interactions and biodiversity within seascapes. Issue 4 (3rd April 2022) - Bugnot, Ana B.; Dafforn, Katherine A.; Coleman, Ross A.; Ramsdale, Megan; Gibbeson, Jayden T.; Erickson, Katherine; Vila‐Concejo, Ana; Figueira, William F.; Gribben, Paul E.
Abstract: Habitat interactions play key roles in regulating biodiversity and ecosystem functions. This is particularly important in aquatic ecosystems, where the flow of water facilitates exchanges of energy and matter. Oyster reefs, a highly degraded habitat globally and a key focus for restoration efforts, can reduce water movement and facilitate the deposition of particles around them, affecting nutrient cycling in surrounding sediments. The effects of these reefs on sediment infauna taxonomic and functional biodiversity, however, remain unknown. We sampled sediments at increasing distances from reefs at three estuaries to evaluate the relationships between proximity to oyster reefs and composition and functionality of infaunal communities and explored the potential mechanisms behind those relationships. Sediments close to oyster reefs had consistently greater amounts of labile organic matter, which in turn was positively related to the number of taxa and total abundance of infauna. Also, the functional traits of infauna, such as bioturbation and feeding modes, were related to proximity to reefs, but they were variable between estuaries indicating the importance of background estuarine environmental conditions. These results suggest that habitat linkages between oyster reefs and sediments are important in regulating taxonomic biodiversity, while functional biodiversity seems to be driven by processes operating at larger scales. Given burgeoning restoration initiatives worldwide, particularly those of oyster reefs, incorporating seascape interactions can help inform recovery of biodiversity and functions beyond the target habitat at the seascape level, which is often overlooked.